Expression and immunological role of FUNDC2 in pan-cancer - Xirong Qiu; Shuyu Wang; Chenlu Li; Yinan Wang (PLoS ONE, 2025)
FUNDC2 is a novel mitochondrial protein and is highly involved in various cancers. However, expression pattern and possible role and mechanism of FUNDC2 in pan-cancer remain to be investigated. TIMER 2.0 was used to investigate the expression patterns and immune infiltration of FUNDC2. GEPIA was applied to study the relationship between level of FUNDC2 and prognosis of the patients with pan-cancer. STRING was employed to analyze the potential interacting proteins of FUNDC2. The phosphorylation sites were predicted by cBioPortal and PhosphoNet. Furthermore, variations of FUNDC2 in cancers were investigated by cBioPortal. Finally, AlphaFold was used to predict the structure of FUNDC2. The data show that there were significant differences in the expression levels of FUNDC2 between cancer tissues and controls. Specifically, the levels of FUNDC2 in 8 cancers were significantly lower than the respective controls. The survival time of the cancer patients with higher levels of FUNDC2 was longer than that of lower FUNDC2 in most different types of cancers. The pattern of FUNDC2 was significantly related to immune infiltration of B cells of cancer patients. STRING analysis revealed that FUNDC2 can interact with FUNDC1, et al. Fifteen phosphorylation sites were predicted by PhosphoNet and cBioPortal, of which the S167 also overlapped with the mutation sites of FUNDC2. These data collectively show that the mitochondrial protein FUNDC2 may serve as a possible prognostic biomarker across various cancers and the mechanism may include immune infiltration.